1994
DOI: 10.1111/j.1365-2958.1994.tb01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐surface‐associated polypeptides CshA and CshB of high molecular mass are colonization determinants in the oral bacterium Streptococcus gordonii

Abstract: The human oral bacterium Streptococcus gordonii expresses, on the cell surface, two antigenically related high-molecular-mass polypeptides denoted CshA and CshB, encoded by genes at separate chromosomal loci. The precursor form of CshA is composed of four distinct segments: (i) a 41-amino-acid residue leader peptide, (ii) N-terminal 42-878 residues, (iii) residues 879-2417 comprising 13 repeat blocks of 101 amino acid residues and three shorter blocks, and (iv) a C-terminal anchor domain similar to those prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 40 publications
4
105
0
Order By: Relevance
“…In this study, we have identified FbpA as a second fibronectin-binding protein in oral S. gordonii. The fbpA gene lies immediately downstream of the cshA gene that encodes a major fibronectin-binding protein of S. gordonii (McNab et al, 1994(McNab et al, , 1996.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have identified FbpA as a second fibronectin-binding protein in oral S. gordonii. The fbpA gene lies immediately downstream of the cshA gene that encodes a major fibronectin-binding protein of S. gordonii (McNab et al, 1994(McNab et al, , 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid pPH1704 contained a 2n2 kb S. gordonii DNA fragment, 1n5 kb of which has been shown to encode the carboxy terminus of CshA (McNab & Jenkinson, 1992). The sequence of the remaining 0n7 kb of the S. gordonii DNA fragment was determined and used to design primers for inverse PCR amplification of flanking DNA (McNab et al, 1994). Briefly, S. gordonii DL1 genomic DNA was digested with SspI, selfligated at 3n5 ng µl − " and then used as a template for PCR (Expand High Fidelity System ; Boehringer Mannheim) with the primers CTERM (5h-TTATACAGGACAGAAAACCC3h ; complementary to nucleotides 8298-8317, cshA locus ; GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
“…C. albicans ATCC 10261 was the yeast strain used in this study. Streptococcal cells were grown on TSBY agar (l − " : 20 g trypticase soy broth, 5 g yeast nitrogen broth, 5 g glucose, 20 g agar) or in BHY (l − " : 37 g brain heart infusion, 5 g yeast extract) medium at 37 mC in screw-capped tubes or bottles as stationary cultures (McNab et al, 1994). Late-exponential-phase cultures (OD '!!…”
Section: Methodsmentioning
confidence: 99%
“…This has also been shown recently for isogenic mutants of S. gordonii deficient in production of surface polypeptides CshA and CshB. These mutants had much-reduced cell-surface hydrophobicity but nevertheless adhered normally to experimental salivary pellicles (McNab et al, 1994). In summary, adhesion of strain CN3410 cells to parotid salivary pellicle is not sensitive to trypsin under the conditions employed, is independent of cell-surface hydrophobicity, and does not involve the long or short components of the fibril tufts since these were wholly removed by trypsin treatment of cells.…”
Section: Discussionmentioning
confidence: 59%